Cancer incidence and mortality among the Métis population of Alberta, Canada. Issue 1 (31st January 2016) - Sanchez-Ramirez, Diana C.; Colquhoun, Amy; Parker, Sara; Randall, Jason; Svenson, Lawrence W.; Voaklander, Don
Abstract : Background: Cancer has been identified as a major cause of morbidity and mortality in Canada over the last decade. However, there is a paucity of information about cancer patterns in Aboriginal people, particularly for Métis. This study aims to explore cancer incidence and mortality burden among Métis and to compare disease estimates with non-Métis population. Methods: This population-based descriptive epidemiological study used cancer incidence and mortality data from 2007 to 2012 obtained from Alberta Health Care Insurance Plan (AHCIP) – Central Stakeholder Registry – and Alberta Cancer Registry (ACR). To identify cancer cases in Métis, the ACR was linked with the Métis Nation of Alberta (MNA) Identification Registry. In Métis and non-Métis people, age-standardized cancer incidence and mortality rates were estimated and subsequently compared between both groups. Results: A higher incidence of bronchus/lung cancer was found among Métis men compared with their non-Métis counterparts (RR=1.69, CI 1.28–2.09; p=0.01). No other statistically significant differences in cancer incidence or mortality were found between Métis and non-Métis people living in Alberta over the course of the 6 years studied. Conclusions: Overall incidence and mortality associated with cancer were not higher among Métis people compared with non-Métis people. However, special efforts should be considered to decrease the higher incidence of bronchus/lung cancer in Métis men. Further development and maintenance of new and existing institutional collaborations are necessary to continue cancer research and health status surveillance in Métis population.